STUDI ETNOGRAFI INTERNALISASI NILAI-NILAI PENDIDIKAN ISLAM MODERAT PADA MASYARAKAT MULTIKULTURAL DI TLOGOPARUT - GRESIK: Studi Etnografi Internalisasi Nilai-Nilai Pendidikan Islam Moderat Pada Masyarakat Multikutural Di Tlogoparut - Gresik - Al Fa'iq, Izzatul Laily; Yenuri, Ali Ahmad (Piwulang: Jurnal Pendidikan Agama Islam, 2025)
Islamic education in a multicultural society has an important role in building tolerance, openness, and social harmony. Cultural and religious diversity demands an inclusive Islamic education approach to create a peaceful and respectful society. This article discusses the concept of Islamic education in a multicultural society as well as strategies for internalizing moderate Islamic values through community-based programs. Using an ethnographic approach, this study aims to describe how community-based Islamic education programs, such as recitation, lectures, and faith-based social activities, can help instill Islamic moderation values in people's lives. The results of the study show that communities that have community-based Islamic education programs are more likely to develop attitudes of tolerance and openness than communities without similar programs. Although there are various challenges in its implementation, such as cultural resistance and limited resources, solutions can be found through strengthening the capacity of educators, collaboration between educational institutions and the government, and the use of technology in supporting moderate Islamic education.